Issues and initiatives of librarianship (Akansha Publishing House, 2005)
Contents of material: 1/ Digital library issuce. 2/ Library functional initiatives. 3/ Responsibilities of librarians. 4/ Technological boost in librianship. 5/ Electronic journal initiatives. 6/ Challenges of librarianship.